2012
DOI: 10.1152/japplphysiol.00663.2011
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity training improves airway responsiveness in inactive nonasthmatic children: evidence from a randomized controlled trial

Abstract: these results suggest that in nonasthmatic prepubescent children, inactivity negatively impacts airway responsiveness, which can be improved with high-intensity training. Excess adiposity, however, may constrain these improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Specifically, two studies that were assessed to be of low risk of bias, Tjønna et al [23] and Racil et al [30], reported significant improvements in both SBP and DBP following the intervention, although it is pertinent to note the low effect sizes associated with the improvements reported for SBP and DBP in Racil et al [30] (Table 5). Whilst the remaining studies [28, 29, 44] reported no significant differences, they demonstrated a trend towards a lower SBP and DBP. Interestingly, Boddy et al [44], demonstrating methodological rigour through a low risk of bias, found an increase in both DBP and SBP in the HIIT group and reductions in the control group, though not significant.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, two studies that were assessed to be of low risk of bias, Tjønna et al [23] and Racil et al [30], reported significant improvements in both SBP and DBP following the intervention, although it is pertinent to note the low effect sizes associated with the improvements reported for SBP and DBP in Racil et al [30] (Table 5). Whilst the remaining studies [28, 29, 44] reported no significant differences, they demonstrated a trend towards a lower SBP and DBP. Interestingly, Boddy et al [44], demonstrating methodological rigour through a low risk of bias, found an increase in both DBP and SBP in the HIIT group and reductions in the control group, though not significant.…”
Section: Resultsmentioning
confidence: 96%
“…Seven studies were considered to have a high risk of bias [22, 24, 25, 29, 40, 41, 45], whereas only two [28, 43] and four [23, 30, 42, 44] studies were considered to have some or low risk of bias, respectively. In studies deemed to have a high or some risk of bias [22, 24, 25, 28, 29, 40, 41, 43, 45], the bias arose from the randomisation process (domain A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 This demonstrates an important benefit of VPA considering asthma is the most common chronic disease among youth. 28 Intervention players in the current study spent approximately 11.5 min of practice time in VPA each practice at follow-up, exceeding the amount of VPA that previous studies have suggested for players to incur health benefits. 26,27 Motivation is an important factor in OYS because it can affect youth's experiences and likelihood of participating in OYS in the future.…”
Section: Outcomementioning
confidence: 92%